Interaction between a haptoglobin genetic variant and coronary artery disease (CAD) risk factors on CAD severity in Singaporean Chinese population - Xuling Chang; Rajkumar Dorajoo; Yi Han; Ling Wang; Jianjun Liu; Chiea‐Chuen Khor; Adrian F. Low; Mark Yan‐Yee Chan; Jian‐Min Yuan; Woon‐Puay Koh; Yechiel Friedlander; Chew‐Kiat Heng (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Haptoglobin (Hp) is a plasma protein with strong anti‐inflammation and antioxidant activities. Its plasma level is known to be inversely associated with many inflammatory diseases, including cardiovascular diseases. However, the association of HP genetic variants with coronary artery disease (CAD) severity/mortality, and how they interact with common CAD risk factors are largely unknown. Methods We conducted the analysis in a Singaporean Chinese CAD population with Gensini severity scores (N = 582) and subsequently evaluated the significant findings in an independent cohort with cardiovascular mortality (excluding stroke) as outcome (917 cases and 19,093 controls). CAD risk factors were ascertained from questionnaires, and stenosis information from medical records. Mortality was identified through linkage with the nationwide registry of births and deaths in Singapore. Linear regression analysis between HP genetic variant (rs217181) and disease outcome were performed. Interaction analyses were performed by introducing an interaction term in the same regression models. Results Although rs217181 was not significantly associated with CAD severity and cardiovascular mortality (excluding stroke) in all subjects, when stratified by hypertension status, hypertensive individuals with the minor T allele have more severe CAD (β = 0.073, SE = 0.030, p = 0.015) and non‐hypertensive individuals with the T allele have lower risk for mortality (odds ratio = 0.771 (0.607–0.980), p = 0.033). Conclusion HP genetic variant is not associated with CAD severity and mortality in the general population. However, hypertensive individuals with the rs217181 T allele associated with higher Hp levels had more severe CAD while non‐hypertensive individuals with the same allele had lower risk for mortality in the Chinese population.